The Bailey Point Region and Other Muskox Refugia in the Canadian Arctic: A Short Review - Thomas, D.C.; Miller, F.L.; Russell, R.H.; Parker, G.R. (ARCTIC, 1981)
The muskox (Ovibos moschatus) is widely distributed over much of arctic Canada but only at a few locations do their densities remain high and populations relatively stable. These refugia constitute the most favourable muskox ranges in the Canadian Arctic Archipelago . Refugia for muskoxen in the High Arctic include lowlands on eastern Axel Heiberg Island in the Mokka Fiord region, the lowlands of northeastern Devon Island, and the Bailey Point region of Melville Island . All of those regions historically have supported high densities of muskoxen from time to time but the Bailey Point region must be considered the best habitat for muskoxen in the Canadian High Arctic. .